Case Report : Eritema Nodosum Leprosum pada Pasien Pasca Terapi Kusta Tipe MB dengan Kecacatan Tingkat 2 - Mohamad Mimbar Topik; Mumtaz Alvira (Lembaga Pengembangan Kinerja Dosen, 2025)
Erythema nodosum leprosum (ENL) is a type 2 leprosy reaction caused by the humoral immune response of Mycobacterium leprae, which results in inflammatory nodules on the skin that can lead to nerve and organ damage. One of the immune-mediated complications of leprosy and severe multisystem lepromatous leprosy is known as type 2 leprosy reaction or erythema nodusum leprosum (ENL). Risk factors for ENL can be influenced by age, educational attainment, socioeconomic status, and gender. ENL causes high morbidity and mortality and usually requires immediate medical attention. We report a case of ENL with grade 2 disability in a clinically diagnosed Multibacillary (MB) leprosy patient who had had leprosy for 20 years.